Traditional Medicinal Herbs and Food Plants Have the Potential to Inhibit Key Carbohydrate Hydrolyzing Enzymes In Vitro and Reduce Postprandial Blood Glucose Peaks In Vivo - M. Fawzi Mahomoodally; A. Hussein Subratty; A. Gurib-Fakim; M. Iqbal Choudhary; S. Nahar Khan (The Scientific World Journal)
We hypothesized that some medicinal herbs and food plants commonly used in the management of diabetes can reduce glucose peaks by inhibiting key carbohydrate hydrolyzing enzymes. To this effect, extracts of Antidesma madagascariense (AM), Erythroxylum macrocarpum (EM), Pittosporum senacia (PS), and Faujasiopsis flexuosa (FF), Momordica charantia (MC), and Ocimum tenuiflorum (OT) were evaluated for α-amylase and α-glucosidase inhibitory effects based on starch-iodine colour changes and PNP-G as substrate, respectively. Only FF and AM extracts/fractions were found to inhibit α-amylase activity significantly (P<0.05) and coparable to the drug acarbose. Amylase bioassay on isolated mouse plasma confirmed the inhibitory potential of AM and FF extracts with the ethyl acetate fraction of FF being more potent (P<0.05) than acarbose. Extracts/fractions of AM and MC were found to inhibit significantly (P<0.05) α-glucosidase activity, with IC50 comparable to the drug 1-deoxynojirimycin. In vivo studies on glycogen-loaded mice showed significant (P<0.05) depressive effect on elevation of postprandial blood glucose following ingestion of AM and MC extracts. Our findings tend to provide a possible explanation for the hypoglycemic action of MC fruits and AM leaf extracts as alternative nutritional therapy in the management of diabetes.